Physical Literacy Profile of Students at Titian Teras High School H. Abdurrahman Sayoeti - Handika Bayutama; Ilham; Reza Hadinata (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Physical literacy is an important aspect in supporting student engagement in physical activities on an ongoing basis. Information about students' physical literacy profiles is needed as a basis for developing physical education learning in schools. This study aims to determine the physical literacy profiles of students at SMAN Titian Teras H. Abdurrahman Sayoeti. This study used a quantitative descriptive method. The research subjects consisted of 117 students at SMAN Titian Teras H. Abdurrahman Sayoeti. Data collection was carried out using an instrument adapted from the Adolescence Physical Literacy Questionnaire (APLQ). Data analysis used descriptive percentage techniques. The results showed that the students' physical literacy profile was in the very good category at 17.09%, the good category at 50.43%, the moderate category at 29.91%, the poor category at 1.71%, and the very poor category at 0.85%. These findings indicate that the majority of students have a good level of physical literacy, reflecting their abilities, motivation, cognitive and affective aspects in performing physical activities. Based on the research results, it can be concluded that the physical literacy profile of students at SMAN Titian Teras H. Abdurrahman Sayoeti is generally in the good category.